Perspective on Digital Marketing Toward Purchase Intention: A Sentiment Analysis - Kamsinah; Miftahkhus Surur (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to determine the sentiment towards digital marketing and its influence on purchasing tendencies over the last ten-year period, starting from 2014 to 2023. The method used is descriptive statistical analysis with meta-analysis and sentiment from secondary data in the form of metadata from 92 articles indexed by Dimention.ai with data processing using Microsoft Excel 2016 and SentiStrength. The results of the sentiment analysis show that the experts' perceptions of the influence of digital marketing on purchase intentions have a positive sentiment of 63.0%, a negative sentiment of 10.9%, and the remaining neutral sentiment of 25.0%. These findings indicate that the trend of digital marketing on purchase intentions continues to increase and can provide a better understanding of the role of digital marketing in influencing purchase intentions. This research also provides practical guidance for marketing practitioners in designing more effective digital marketing strategies.